2004
DOI: 10.1086/380609
|View full text |Cite
|
Sign up to set email alerts
|

Time Development of Recurrent Nova CI Aquilae's 2000 Outburst between 0.8 and 2.5 MICRONS

Abstract: We report 0.8-2.5 m spectrophotometry of CI Aquilae at eight epochs between 2000 May 9 and 2001 June 2 UT, corresponding to approximately 3 and 391 days after peak brightness. Near peak brightness, the spectra showed emission lines that were characteristic of a low-excitation, nitrogen-rich shell. Within a few weeks, the spectra began to show higher excitation/ionization emission lines indicative of a harder illuminating source: the neutral metal lines faded, leaving only lines of H i, He i, and He ii and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…These results agree with ours within the limits of the errors. On the other hand, Lynch et al (2004) found a higher value E(B − V) = 1.5 ± 0.15 from the ratios of the near-infrared O I lines. The cause of the disagreement with our result is not known.…”
Section: Interstellar Absorption Lines and Bandsmentioning
confidence: 81%
See 3 more Smart Citations
“…These results agree with ours within the limits of the errors. On the other hand, Lynch et al (2004) found a higher value E(B − V) = 1.5 ± 0.15 from the ratios of the near-infrared O I lines. The cause of the disagreement with our result is not known.…”
Section: Interstellar Absorption Lines and Bandsmentioning
confidence: 81%
“…Therefore, its distance may be less than or does not exceed much 1 kpc at maximum. Absolute V magnitudes of light maxima higher than −7 mag were derived for the outbursts in 1917 and 2000 from the decline rates of luminosity: those are M V = −7.35 ± 0.2 mag by Kiss et al (2001), M V = −7.4 mag by Burlak & Esipov (2001), and M V = −7.55 ± 0.5 mag by Lynch et al (2004). If we adopt the observed maximum luminosity m V = 9.0 mag (Kiss et al 2001) or m V = 8.8 mag (Burlak & Esipov 2001) for the outburst in 2000, the above derived absolute maximum luminosities give distances larger than 4.5 kpc, adopting A V = 2.9 mag.…”
Section: Distance To CI Aqlmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 for line identifications in the 0.8-4.5 μm region). The six unidentified lines that frequently appear in novae at 1.1114, 1.1901, 1.5545, 2.0996, and 2.425 μm (Williams et al 1996;Lynch et al 2001Lynch et al , 2004 were not evident. On or immediately after 2006 November 30, dust formed and changed the spectral energy distribution (SED) of the nova shell.…”
Section: Observationsmentioning
confidence: 89%